CMV, B and C hepatitis among multi-transfused hereditary hemolytic Anemia children: an updated Egyptian experience - Laila M. Sherief; Seham M. Ragab; Mohamed A. Helwa; Naglaa M. Kamal; Mona R. Afify; Rasha T. S. Mohammed; Ghada Abd Elmoniem Mokhtar; Hanan S. Sherbiny (BMC, 2021)
Abstract Background and objectives Regular blood transfusion has improved the overall survival and quality of life for patients with hereditary hemolytic anemias. Nevertheless, it carries a real risk of acquisition of blood-borne virus infections, especially viral hepatitis. The purpose of the current study is to present an Egyptian update on blood-borne hepatitis C & B viruses (HCV & HBV) and cytomegalovirus (CMV) among multi-transfused Egyptian children with hereditary hemolytic anemias, especially after implementation of national preventive programs in Egypt. Patients and methods All pediatric patients with hereditary hemolytic anemias who have regular follow-up and received frequent blood transfusion at the Pediatric Hematology Units, Menuofia and Zagazig Universities Hospitals, Egypt, during the study period, were recruited. They were tested for hepatitis B surface antigen (HBVsAg), hepatitis C antibody (HCVab), and CMV immunoglobulin M (IgM) serology. Those with positive results were confirmed by real-time polymerase chain reaction (PCR). Results Four hundred and seventy-seven hereditary hemolytic anemia patients fulfilled the study inclusion criteria. Their ages ranged from 2 to 18 years, 54.9% of them were males. Seroprevalence of HCVab and CMV-IgM were (14.7% & 6.7% respectively) and they were confirmed by PCR. None of the studied cases were HBVsAg positive. Seropositivity for HCV was significantly associated with older age of the patients, higher transfusion frequency, longer disease duration, and higher mean serum ferritin. Conclusion HCV followed by CMV infections still represent a significant problem for patients with hereditary hemolytic anemias. Nationwide plans should be taken to ensure meticulous and highly sensitive methods of blood screening before transfusion. On the other hand, it seems that HBV compulsory vaccination had succeeded to eliminate HBV infection.